Trends in Engineering Management Education From 2011–2015. Issue 1 (2nd January 2017) - Daughton, William
Abstract: The American Society for Engineering Education provides comprehensive data on enrollment and graduation rates for all engineering fields at the Bachelor's, Master's, and PhD levels. In addition, data are provided on the demographics of the various fields. This information, coupled with Accreditation Board for Engineering and Technology data, presents an opportunity to explore the trends in higher education in Engineering Management in the last five years. Contrasts to earlier times and implications for the future are presented as a result of the analysis of these trends.